Corruption in Contemporary Politics
XIV, 274 p.
Keywords: Political corruption has recently emerged as a key area in the study of advanced industrial nations. Not only has it become more visible than in the past, its sheer scale in some countries has had a significant impact on the functioning of their political institutions. Martin Bull and James Newell have assembled a group of experts to address the importance of this phenomenon for contemporary Western democracies - as well as for the new democracies of Eastern Europe, for the European Union and at the international level.